Marketing 0.0 dan Trust Economy: Reposisi Kepercayaan sebagai Kondisi Pra-Keputusan dalam Teori Pemasaran - Sani Gazali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This article proposes Marketing 0.0 as a fundamental conceptual repositioning of marketing theory rooted in the Trust Economy framework. Unlike mainstream marketing theory, which positions trust as an outcome of communication, persuasion, or brand reputation, cross-disciplinary studies in economics, sociology, and neuroscience suggest that trust functions as a pre-decisional condition that precedes market exchange. This research employs a conceptual-theoretical methodology, synthesizing transaction cost theory, social capital, neuroeconomics, and contemporary trust literature. The article's primary contribution is formalizing the shift in trust's position from a dependent variable to an ontological gateway in marketing decision-making. Marketing 0.0 is positioned not as a stage in marketing evolution, but rather as a conceptual ground zero that enables continuous tactical adaptation without reliance on pseudo-novelty. The article concludes with theoretical and practical implications for the development of marketing science in an era of uncertainty and information saturation.